Virtual Reality Remote Access Laboratory for Teaching Programmable Logic Controller Topics - (:unkn) unknown (TEMPUS PUBLICATIONS, 2020)
This study is concerned with improving the effectiveness and quality of technical education through the use of virtual reality technology. To do so, we have examined the effects of an application of a Virtual Reality-Supported Remote Access Laboratory (VRRALAB) system we developed using remote access and virtual reality technologies on students' learning experience. The advantage of such a remote access laboratory is that use of equipment that requires experience, such as working under high voltage, can be hazardous to novice users, whereas interactively using a real device from a virtual reality-supported remote access laboratory environment comes with no such risk. We have used an experimental design with 74 associate degree mechatronics program second class students who were divided into the control and experiment groups. They were enrolled on the same Programmable Logic Controller (PLC) course using the applications prepared for VRRALAB design. The experimental group was given a 4-hour training session using the basic subjects of a PLC lesson with the VRRALAB application with a traditional method, whilst the control group was taught only in conventional fashion. Both the control and experiment groups were assessed using the same exam questions. It was found that students who studied with VRRALAB were more successful than those who did not. Satisfaction levels among students using VRRALAB were also found to be high when measured by a questionnaire survey. The results indicate that remote access laboratories using virtual reality are likely to increase the quality of learning and satisfaction levels.
Keywords: virtual reality; augmented reality; remote lab; PLC training; education; AUGMENTED REALITY; ENGINEERING-EDUCATION; LABS